The anthropogenic impacts on the aquatic resources of Batang Kayan, Lundu - Adrian Richard, Sageng (Universiti Malaysia Sarawak (UNIMAS), 2004)
The main purpose of this study is to assess the impact of anthropogenic activities towards the aquatic resources in Batang Kayan, Lundu. Water samples were collected all along the Batang Kayan River and its tributaries for physical and chemical analyses. Quantitative and qualitative data collection on fish and fisheries was done through the means of purposive sampling whereby fishermen were chosen as the respondents. It was discovered that the main anthropogenic activities in the area are oil palm plantation, paddy plantation and bridge construction. The results showed that some of the water samples have high COD and total suspended solids. This study also found out that the quantity of fish caught in the area has decreases in recent years. As the water quality of Batang Kayan is still considered to be in good condition, the main cause for the decrease in abundance of aquatic resources may be due to unsustainable methods of capture and over fishing. Fisheries resource management can be implemented in the area to help mitigate the decline of aquatic resources and to maintain the water quality so as to be able to support the aquatic life. Fish stocks study should also be done on a regular basis to monitor and detect any sign of aquatic resource decline.